Rectal carcinoid tumor: diagnosis and management - Viana, Charlene (2019)
The authors present a case of rectal carcinoid tumor in an asymptomatic patient who sought a coloproctology service with the purpose of colorectal cancer prevention. During colonoscopy, a polyp lesion was found in the rectum, and it was resected with a polypectomy loop. Anatomopathological examination revealed a rectal carcinoid tumor with compromised margins. The lesion site was resected again and pathological exam no longer showed neoplasia. A systematic review of the issue was performed, discussing diagnosis aspects, difficulties in the choice of therapeutic approaches, and prognosis. The conclusion is that the rarity of the disease brings difficulties in the choice of treatment; although it has a good prognosis in most cases, its malignant potential cannot be underestimated.